Towards an Anti-Colonial Turn in Science and Mathematics Education: Centering Indigenous Ghanaian Knowledge - Kenneth Gyamerah (Educational Considerations, 2025)
The integration of Indigenous knowledges into education is increasingly recognized as integral to creating culturally relevant and sustaining pedagogies, particularly in mathematics and science. This study explores Ghanaian primary school teachers’ knowledge and understanding of Indigenous Ghanaian knowledges (IGK) and their potential integration into classroom practice. Employing an Indigenous research methodology, data were gathered from 20 teachers through sharing circles, conversational inquiry, and a collaborative co-creation workshop. Findings reveal that teachers hold substantial knowledge of Indigenous epistemologies and recognize their relevance to mathematics and science education. However, in Ghana, significant barriers hinder the integration of these knowledges into formal education. These include a colonially rooted curriculum that marginalizes Indigenous Ghanaian knowledges, limited pedagogical training, and societal misconceptions that frame Indigenous knowledge as unscientific. Teachers articulated three distinct approaches to Indigenous knowledge integration into mathematics and science curricular: the Practical Inclusionist, which views IGK as supplementary; the Critical Incorporationist, which positions IGK as equal to Western knowledge systems; and the Integrativist, which centers IGK as foundational to teaching. Through the co-creation sessions, teachers developed exemplar lesson plans that meaningfully embed their distinct indigenous knowledges in core scientific and mathematical topics. This study highlights both the challenges and possibilities of integrating Indigenous Ghanaian knowledges into formal education and calls for a reimagining of Ghana’s mathematics and science curricula to embrace epistemic plurality and affirm Indigenous knowledges as vital to the future of science and mathematics education.
Keywords: African Indigenous knowledges; African-centred education; STEM learning; Ghana; teachers; decolonization